Performance simulation of multi-stage axial-flow compressor of turbo-shaft engine with account for erosive wear nonlinearity of its blades - V. A. Potapov; A. A. Sanko (Научный вестник МГТУ ГА)
The construction and useful practice of gas-turbine engine diagnosis systems depend largely on the availability of the engine mathematical models and its certain components in their structure. Utilization of multi-stage axial flow compressor performance with account for erosive wear of its parts during the operation fundamentally raises possibilities of such systems as erosive wear of flow channel, blade rings of impellers and vane rings of multi-stage compressor is a common cause of preschedule gas-turbine engine detaching from an aircraft. As evidenced by various contributions presented in the article, special emphasis on abrasive wear impact assessment on axial flow compressor performance is placed upon rotor-wing turbo-shaft engine due to their particular operating conditions. One of the main tasks in the process of mathematic simulation of an axial flow compressor blade ring is consideration of its wear type that again has a nonlinear distribution along the level of the blade. In addition, wear rate at entry and exit blade edges often have different principles. Detecting of these principles and their consideration when constructing the compressor mathematical model is a crucial task in diagnostic assessment and integrity monitoring of rotor-wing turbo-shaft engine in operation. The article represents a concept to an estimate nonlinear erosive wear effect of axial flow compressor blades on its performance based on the three-dimensional flow approach in the gas-air flow duct of compressor with a formulation of the blade rings. This approach renders possible to take into account the nonlinearity of the compressor blades wear during their operation. Through the example of the inlet compressor stage of a rotor-wing aircraft gas-turbine engine, the engine pump properties predictions with different kind of rotor blade wear have been presented.